Nominal or Real? The Impact of Regional Price Levels on Satisfaction with Life - Thomas Deckers; Armin Falk; Hannah Schildberg-Hörisch (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2013)
According to economic theory, real income, i.e., nominal income adjusted for purchasing power, should be the relevant source of life satisfaction. Previous work, however, has only studied the impact of inflation adjusted nominal income and not taken into account regional differences in purchasing power. Therefore, we use a novel data set to study how regional price levels affect satisfaction with life. The data set comprises about 7 million data points that are used to construct a price level for each of the 428 administrative districts in Germany. We estimate pooled OLS and ordered probit models that include a comprehensive set of individual level, time-varying and time-invariant control variables as well as control variables that capture district heterogeneity other than the price level. Our results show that higher price levels significantly reduce life satisfaction. Furthermore, we find that a higher price level tends to induce a larger loss in life satisfaction than a corresponding decrease in nominal income. A formal test of neutrality of money, however, does not reject neutrality of money. Our results provide an argument in favor of regional indexation of government transfer payments such as social welfare benefits.
urn:nbn:de:bvb:19-epub-17488-0
Keywords: D60; C23; D31; 330; Life satisfaction; price index; neutrality of money